2019
DOI: 10.1080/1331677x.2019.1678499
|View full text |Cite
|
Sign up to set email alerts
|

Ultimate owner and risk of company performance

Abstract: The purpose of this paper is to investigate the links between a company's ultimate owner and the risk involved with financial performance. The study tests hypotheses on the relation between ultimate ownership origin and risk of return on assets. The research adopts cross-sectional data from a unique sample of 32,614 companies across 43 European countries with ultimate owners from 105 countries. The results indicate that the domestic ultimate owner is, in general, less likely to be a risk-taker than overseas in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 68 publications
1
10
0
1
Order By: Relevance
“…These implies that companies with higher number of employees and with foreign ownership are more likely to disclose human related information. In addition, these findings are in line with other financial institutions, namely bank disclosure [94] and recent research on the agency issues [95,96] and insurance sector [74]. Ullah et al [74] and Orazalin [94] indicated that ownership is correlated to the extent of corporate social responsibility disclosures in insurance companies.…”
Section: Conclusion and Discussionsupporting
confidence: 79%
“…These implies that companies with higher number of employees and with foreign ownership are more likely to disclose human related information. In addition, these findings are in line with other financial institutions, namely bank disclosure [94] and recent research on the agency issues [95,96] and insurance sector [74]. Ullah et al [74] and Orazalin [94] indicated that ownership is correlated to the extent of corporate social responsibility disclosures in insurance companies.…”
Section: Conclusion and Discussionsupporting
confidence: 79%
“…Being a business owner himself, he presents his own experience with reducing business risk caused by a pandemic. Financial performance in time of Covid-19 also varies across firms depending on ultimate owner risk aversion attitudes (Staszkiewicz & Szelągowska, 2019). Methods firms' implement to monitor key risk indicators also proves important in time of pandemic crisis (Peček & Kovačić, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Regardless of the type of enterprise, controlling shareholders (principals) are riskneutral (Staszkiewicz & Szelągowska, 2019). They employ competent and experienced professional managers (agents) to reduce the production cost 2 .…”
Section: Enterprise Heterogeneity and Manager Differencesmentioning
confidence: 99%
“…Effective decision-making within the enterprises is a widely discussed area both in practice and in the research community (Staszkiewicz & Szelągowska, 2019). The seminal researches related to enterprise strategic behaviour is mainly based on two theories: the principal-agent theory (Fama & Jensen, 1983) and the market competition theory (An & Yang, 2002;Chaim & Pakes, 2000;Porter, 1983).…”
Section: Introductionmentioning
confidence: 99%